V'ANETA Enterprise / Muhammad Amir Hamzah Mohd Yusuf... [et al.] - Mohd Yusuf, Muhammad Amir Hamzah; Ismail, Muhammad Azziq; Mohd Rizal, Nur Izzati; Mohd Padzli, Nur Fadzira; Mohamad Tahir, Nurul Nabihah (2020)
The company V' aneta Enterprise ;s a duvet establishment founded by five of friends which want to share this business together. This five of friends are Nur lzzati Binti Mohd Rizal, Nur Fadzira Binti Mohd Padzli, Nurul Nabihah Binti Mohd Tahir, Muhammad Amir Hamzah Bin Mohd Yusuf and Muhammad Azziq Bin Ismail. This five friends have had experience in the duvet industry since 2010. V' aneta Enterprise was established as an duvet production marketed with a modem style. The company is itself is located in the Selangor. Main competitors of our business are Akemi company, Novelle Company and King Koil Company which are this al comp ny have their regular customer and their products was very famous among people. The market for our products will be centred around the Selangor area, with a population of 6 million people. The reason for this is because the base of our company will be around Selangor as it is an industrial area with a densely populated suburban population. Our production will be done in Selangor area due to the availability of resources that is offered therefore it allows for strategic convenience when providing services to our customers.